Increasing the Health-Related Quality of Life in Children with Congenital Rubella Syndrome: A Mixed-methods Study - Elisabeth Siti Herini; Agung Triono; Kristy Iskandar; Ashadi Prasetyo; Albaaza Nuady; Marissa Leviani Hadiyanto; Kania Diantika; Veronica Wulan Wijayanti; Avianti Pramastuti (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2023)
Introduction: Rubella infection during the first trimester of pregnancy is a significant cause of fetal malformation syndrome, or Congenital Rubella Syndrome (CRS), which affects the children’s quality of life (QoL). A Community Engagement Program was arranged collaboratively to increase the QoL of children with CRS and enhance parents’ skills and knowledge to better care for their children with CRS. Methods: A mixed-method descriptive study was conducted from April to October 2022 at Dr. Sardjito General Hospital. Sample recruitment used the purposive sampling method, which had been clinically and serologically diagnosed with CRS. Children’s QoL data were analyzed with a cross-sectional study design. The tools used were the Pediatric Quality of Life Inventory (PedsQL)TM 4.0 Generic Core Scales and SPSS version 26 to analyze paired T-tests. A focus group discussion (FGD) was used for qualitative thematic analysis. Results: We involved ten members willing to participate voluntarily in the PedsQL assessment and FGD. The result was an increase in patients’ QoL in the Physical Function domain that was statistically significant: pre-test and post-test physical health summary [490 (±261) vs. 510 (±251); p=0.022]. While social, emotional, and school functions increased were not statistically significant. From the FGD, the parents had diverse experiences and understanding of CRS-supporting examinations and treatments needed. Parents felt the children’s growth and development, as social and school functions were the common burdens. In order to help CRS prevention, the parents suggested a more comprehensive premarital program and antenatal care. Conclusions: The Community Engagement Program helps to increase the patient’s QoL in the Physical Function domain. Comprehensive multidiscipline management is needed to support children’s growth, social and educational functions. Periodic evaluations are required to monitor the QoL of children with CRS.